2012
DOI: 10.1111/j.1468-3083.2012.04635.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for treatment of atopic eczema (atopic dermatitis) Part I

Abstract: The existing evidence for treatment of atopic eczema (atopic dermatitis, AE) is evaluated using the national standard Appraisal of Guidelines Research and Evaluation. The consensus process consisted of a nominal group process and a DELPHI procedure. Management of AE must consider the individual symptomatic variability of the disease. Basic therapy is focused on hydrating topical treatment, and avoidance of specific and unspecific provocation factors. Anti‐inflammatory treatment based on topical glucocorticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
473
2
61

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(540 citation statements)
references
References 171 publications
(189 reference statements)
4
473
2
61
Order By: Relevance
“…In addition, NTP-CE incorporates a lipid lamellar technology resembling naturally occurring skin barrier lipids. To become a useful adjunct in the management of AD and other conditions associated with dry skin, NTP-CE has to provide skin-moisturizing potential (3). Findings of an initial set of two studies in healthy adult subjects suggested that twicedaily application of NTP-CE is well tolerated and associated with significant improvements in skin barrier restoration, skin moisturization, and intercellular lipid layer (ICLL) organization in the stratum corneum (SC).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NTP-CE incorporates a lipid lamellar technology resembling naturally occurring skin barrier lipids. To become a useful adjunct in the management of AD and other conditions associated with dry skin, NTP-CE has to provide skin-moisturizing potential (3). Findings of an initial set of two studies in healthy adult subjects suggested that twicedaily application of NTP-CE is well tolerated and associated with significant improvements in skin barrier restoration, skin moisturization, and intercellular lipid layer (ICLL) organization in the stratum corneum (SC).…”
Section: Introductionmentioning
confidence: 99%
“…Глюкокортикостероиды имеют многочисленные эф -фекты при воздействии на кожу [32][33][34]. Молекула сте-роида после поглощения связывается с цитоплазмати-ческим рецептором в кератиноцитах, который затем проникает в ядро, воздействуя на транскрипцию рибо-нуклеиновой кислоты.…”
Section: топические глюкокортикостероидыunclassified
“…Плацебо-контролируемыми клиническими иссле-дованиями было показано, что суммарный эффект применения топических ГКС или ингибиторов кальциневрина вносит основной вклад в улучшение состояния больных АтД. Дополнительное введение антибиотиков и/или антимикотиков лишь незначи-тельно улучшало динамику выздоровления [59][60][61][62][63]. С учетом риска развития устойчивости к антибио-тикам современные рекомендации по лечению АтД во всем мире предлагают ограничить использование противоинфекционной терапии.…”
Section: терапия аллергодерматозовunclassified
“…Включение антибактериальной терапии целесо-образно при распространенном процессе, явных признаках наличия той или иной инфекции и у больных, не отвечающих на базисную терапию [59][60][61]. В последнем случае применение антибиотиков и антимикотиков будет значимым в снижении реак-тивности иммунной реакции на повреждение кож-ного барьера (см.…”
Section: терапия аллергодерматозовunclassified